Modernization of Islamic Education Azyumardi Azra Perspective - Nur Huda (Tarbiyah Departement collaboration with AMCA, 2019)
The challenges of the 21st century, however, demand an appropriate response from the whole Islamic education system. If Muslims, including in Indonesia, do not want to just survive in the midst of increasingly fierce and tighter global competition, but also hope to be able to come forward, then the reorientation of thinking about Islamic education and the restructuring of systems and institutions is clearly a necessity. The perspective of science and technology which appears to be unsustainable. Then a reformer thought is needed in the world of Islamic education. The concept of modernization of Isla education Azyumardi Azra's view is a concept that is worth discussing.